Industrial Revolution (IR) 4.0 innovations / Jamal Othman... [et al.] - Othman, Jamal; Kadar, Rozita; Mohamed Yusoff, Sharifah Adilah; Abdul Wahab, Naemah; Umar, Norazah (Unit Penulisan Dan Penerbitan JSKM, 2022)
The introduction of Industrial Revolution (IR) 4.0 has brought the creation of innovation either in industries or people’s daily life. The implementation of IoT, cloud computing, grid computing, big data and other new fields of IT applications has benefited the manufacturing industries, services in government and corporate agencies as well as the whole human life. As the manufacturing sectors focus to increase productivity by utilising the existing technology or assets, it is believed that IR 4.0 is capable to achieve the goals, vision and mission of the organisations. This paper aims to introduce and explain in detail nine (9) elements of IR 4.0. Furthermore, examples of application for each element are further discussed in terms of industrial, government and human being practices. Implementation of IR 4.0 in education is believed to increase the teaching and learning pedagogies effectiveness, especially in the e-learning area. Nevertheless, to ensure that the dreams can come true, the infrastructures and info structures should be established into Industrial Revolution (IR) so that they can be implemented effectively and able to benefit the organisations and people.